A new class of highly efficient exact stochastic simulation algorithms for chemical reaction networks - Ramaswamy, Rajesh; González-Segredo, Nélido; Sbalzarini, Ivo F (The Journal of chemical physics, 2009)
We introduce an alternative formulation of the exact stochastic simulation algorithm (SSA) for sampling trajectories of the chemical master equation for a well-stirred system of coupled chemical reactions. Our formulation is based on factored-out, partial reaction propensities. This novel exact SSA, called the partial-propensity direct method (PDM), is highly efficient and has a computational cost that scales at most linearly with the number of chemical species, irrespective of the degree of coupling of the reaction network. In addition, we propose a sorting variant, SPDM, which is especially efficient for multiscale reaction networks.